Zapoteca portoricensis root crude methanol extract and its fractions normalizes aberrations associated with benign prostatic hyperplasia in rats. Issue 1 (1st January 2020) - Ikeyi, Adachukwu Pauline; Okagu, Innocent Uzochukwu; Ezeanyika, Lawrence Uchenna Sunday; Alumanah, Edwin Olisah
Abstract : This study investigated the application of crude methanol extract (CME) of Zapoteca portoricensis root and its methanol (MF) and ethyl acetate (EAF) fractions in managing benign prostatic hyperplasia (BPH). Forty-five albino rats (180-200 g) were divided into nine groups of five rats each: Group 1 served as normal control. BPH was induced in groups 2–9 using dihydrotestosterone and estradiol. Group 2 served as BPH-control and group 3 was dutasteride-treated. Groups 4 and 5, 6 and 7, and 8 and 9 were respectively treated with 200 and 400 mg/kg/d b.w. of CME, 200 and 400 mg/kg/d b.w. of MF, and 200 and 400 mg/kg/d b.w. of EAF, respectively for 14 days orally. The effects of the extracts on the hematological and biochemical indices of the rats were assessed. At 400 mg/kg/d b.w, p.o. using a gavage, CME, MF and EAF decreased prostatic specific antigen by 55.91%, 57.54% and 56.75%, respectively comparable to 58.80% by dutasteride (an indication of improved prostate status). The extracts also restored BPH-modified hematological and biochemical status of BPH-induced-extracts-treated rats compared to BPH-control. These findings suggest that Z. portoricensis root extracts normalize aberrations associated with BPH and may justify the plant's folkloric use in the management of BPH.